Communicative intentions of child-directed speech in three different learning environments: Observations from the Netherlands, and rural and urban Mozambique. Issue 4 (October 2015) - Vogt, Paul; Mastin, J. Douglas; Schots, Diede M. A.
This article compares the communicative intentions observed in the speech addressed to children of 1;1 and 1;6 years old from three cultural communities: the Netherlands, rural Mozambique, and urban Mozambique. These communities represent two prototypical learning environments and a third hybrid: Western, urban, middle-class families; non-Western, rural, subsistence-farming families; and non-Western, urban learning environment. The results show that the Dutch CDS contains relatively more utterances with a cognitive intention than the Mozambican CDS. In Mozambique, CDS contains more imperatives, particularly in the rural environment. The CDS from urban Mozambique contains more socioemotional intentions. The findings suggest that these differences can be explained in terms of the different responsibilities and levels of autonomy expected from children of the three learning environments.